Association of hypertension with consumption of energy drinks in an adolescent male - ., Kanuja; Pathak, Vineet Kumar; Chamola, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2023)
Use of energy drinks has dramatically increased in recent times. Athletes, teenagers and students being the most common population who consume it. Users believe that they are a source of instant energy but are unaware of its high Caffeine content resulting in severe adverse effects on health. We reported the case of a young boy who presented with palpitations and high blood pressure after a recent start of energy drink consumption. He had been consuming ‘monster’ energy drink on regular basis as his annual sports meet was round the corner and he had to practise for hours for an upcoming football match. His medical examination revealed Sinus tachycardia and high blood pressure on more than 3 occasions. Rest of the physical examination and lab workup was within normal limits. His pulse and blood pressure returned to normal range after discontinuing ‘monster’ energy drink usage and he was counselled on adverse effects of such products. Several studies have reported numerous health hazards including cardiac effects associated with energy drinks. Labels should be made on these drinks and Caffeine content should be mentioned along with adverse effects on health. Caution for use in children and pregnant or expecting patients should also be mentioned.